2019
DOI: 10.3390/ani9100736
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects against Restraint Stress Effects on Stomach and Spleen in Adult Male Mice

Abstract: Simple SummaryThe current project was designed to examine the effects of restraint stress on body weights, food and water consumption, and pathophysiology of the stomach and spleen in adult mice, and potential roles of the phenolic compound resveratrol during treatment. We found that restraint stress (which is known to be a mixture of psychologic and physical stress) caused a reduction in body weight, food and water consumption, and morphologic changes in the stomach and spleen, which could lead to gastritis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 75 publications
(79 reference statements)
1
9
0
Order By: Relevance
“…Previous reports indicated that corticosterone activated glycogen synthase kinase-3β (GSK-3β) through suppression of phosphoinositide 3-kinases (PI3K)/Akt signaling, in turn suppressed LTP in the hippocampus [ 30 , 31 ]. Therefore, to test if Akt signaling is involved in the effect of HM, we utilized LY294002, a PI3K/Akt signaling inhibitor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports indicated that corticosterone activated glycogen synthase kinase-3β (GSK-3β) through suppression of phosphoinositide 3-kinases (PI3K)/Akt signaling, in turn suppressed LTP in the hippocampus [ 30 , 31 ]. Therefore, to test if Akt signaling is involved in the effect of HM, we utilized LY294002, a PI3K/Akt signaling inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact mechanism of how GR activation regulates synaptic function is still not clear. Several studies report that signaling mechanisms such as caspase-3, Akt, and GSK-3 are involved in the negative role of corticosterone [ 30 , 47 ]. In this study, it was confirmed that prolonged restraint stress increased blood corticosterone, and it was confirmed that HM and thunberginol C inhibit corticosterone-induced neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the chronic restraint stress model is one that has been widely used. However, these models have some defects, including subjectivity, complexity in influencing factors, large variability, and being time-consuming and laborious in operation [30]. In addition, a chronic mild stress (CMS) model is also widely used in simulated stress tests.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (Sigma Chemical Co., St Louis, MO, USA) was diluted to 5% in the vehicle (CMC, sodium carboxymethyl cellulose) [33,34]. The Beijing Institute for Pharmacology and Toxicology (China) supplied sodium carboxymethyl cellulose with trans-resveratrol for oral gavage at 0.5% in CMC.…”
Section: Drugsmentioning
confidence: 99%